2019
DOI: 10.1186/s12871-019-0821-8
|View full text |Cite
|
Sign up to set email alerts
|

Supraglottic jet oxygenation and ventilation for obese patients under intravenous anesthesia during hysteroscopy: a randomized controlled clinical trial

Abstract: Background Supraglottic jet oxygenation and ventilation (SJOV) can effectively maintain adequate oxygenation in patients with respiratory depression, even in apnea patients. However, there have been no randomized controlled clinical trials of SJOV in obese patients. This study investigated the efficacy and safety of SJOV using WEI Nasal Jet tube (WNJ) for obese patients who underwent hysteroscopy under intravenous anesthesia without endotracheal intubation. Methods A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
17
3
Order By: Relevance
“…In this research, the incidence of adverse events was lower than previous reported 10,20 . Among the 150 patients, only 7 patients developed intra-operative hypoxemia, which was relatively short and the oxygenation was effectively improved after treatment.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In this research, the incidence of adverse events was lower than previous reported 10,20 . Among the 150 patients, only 7 patients developed intra-operative hypoxemia, which was relatively short and the oxygenation was effectively improved after treatment.…”
Section: Discussioncontrasting
confidence: 66%
“…Supraglottic jet ventilation (SJV) was also superior toconventional means of oxygen delivery in obese patients under intravenous anesthesia 10 . However, it is unclear whether jet ventilation is superior to COT in maintaining intra-operative oxygenation in patientswith airway stenosis during BI under deep sedation.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the incidence of adverse events was lower than that previous reported [10,20]. Among the 150 patients, only seven developed intra-operative hypoxemia, which was relatively short and the oxygenation was effectively improved after treatment.…”
Section: Discussioncontrasting
confidence: 48%
“…High-ow oxygen through nasal cannula or mask was used among patients infected with COVID-19 associated with severe hypoxemia, and it showed reductions in the need for therapeutic escalation and intubation among patients who received high-ow oxygen [9]. Supraglottic jet ventilation (SJV) was also superior to conventional means of oxygen delivery among patients with obesity who were under intravenous anesthesia [10]. However, whether jet ventilation is superior to COT in maintaining intra-operative oxygenation is unclear among patients with airway stenosis during BI under deep sedation.…”
Section: Introductionmentioning
confidence: 99%
“…High-flow oxygen through nasal cannula or mask was used among patients infected with COVID-19 associated with severe hypoxemia, and it showed reductions in the need for therapeutic escalation and intubation among patients who received high-flow oxygen [ 9 ]. Supraglottic jet ventilation (SJV) is also superior to conventional means of oxygen delivery among patients with obesity who are under intravenous anesthesia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%